The Role of Business Process Innovation in Sustainable Economic Growth: Integrating Technology, Efficiency, and Resilience - Shestakovska, Tetiana; Liashenko, Oksana; Dluhopolskyi, Oleksandr; Duka, Anastasiia; Mykhailovska, Olena; Filipova, Nataliia (European Journal of Sustainable Development, 2025)
Modern economies are driven by a transformative aspect of digitalisation encompassing digitalisation in business operations, which has become a force of efficiency, innovation and new forms of sustainable economic growth. Using digital technologies helps a company streamline workflows, enhance decisions based on data analytics, and improve its competitiveness in local and global markets. Businesses that recognise that they need to adopt digital transformation will enjoy a drastic advantage as they go through a breakneck pace of technological advancement and stand to cut costs, increase productivity, and expand new revenue streams. This research investigates the significant influence of the financial information businesses digitalise on economic growth; it looks at areas like automation, artificial intelligence, cloud computing, and digital platforms. The research centres on how digitalisation affects business scalability and market accessibility and the development of business models for medium-sized enterprises (SMEs). Moreover, it examines how digitalisation makes a society economically resilient, especially during global disruptions, including financial disruptions or geopolitical controversies. Digital transformation brings about immense benefits but comes with risks of cybersecurity problems, digital divides, and the need for continuous upskilling of their workforce. This paper proposes how businesses and policymakers can overcome these barriers to realise the maximum economic benefits of digitalisation. Furthermore, case studies and longitudinal analysis of the digital transformation effects on the business performance are included to enhance empirical grounding of this study. Based on the historical data from the digitally advanced economies like South Korea and Germany, the methodology incorporates GDP impact assessment. Sector focused comparative pre and post digitalisation performance metrics are also presented in addition to the economic benefits that quantify the digital adoption. The methodology adopted in this study consists of statistical analysis of statistical data, market trend analysis, and analysis of reports of analytical agencies alongside case studies and a comparison of business performance before and after digital adoption. SWOT analysis, trend forecasting, and other types of risk assessment are used to obtain better insights into the economics of digital transformation. The study confirms that digital technology integration is a fundamental element in boosting economic efficiency, global competitiveness, and long-term stability of the economy. The involvement of digitalisation in business operations in every industry of the world is increasing. Hence, the importance of digitalisation is increasing, making it crucial for organisations, the government, and stakeholders to adopt and optimise digital strategy. Keywords: digitalisation, business operations, economic growth, digital transformation, automation, business strategy, innovation